Characteristics of solar energy radiation on typical summer and winter days in Kuwait - Bou-Rabee, M.A. (Universiti Malaysia Pahang, 2015)
The energy received by solar collectors for power generation is limited to various conditions. The average data on solar irradiation are normally used to determine the potential of solar energy at any location. However, the variation of solar energy due to seasonal differences could affect the actual performance of the collectors, consequently leading to poorly justified system installations, which are high in cost. In this work, the characteristics of solar energy radiation in Kuwait were studied by measuring irradiance and comparing the data of selected time periods in two extreme seasons. A pyranometer, mounted two meters above the ground on a tubular beam in a shade-free area at a solar energy laboratory in Kuwait was used to measure irradiance on three consecutive days in summer and winter. The radiation data were recorded at five-minute intervals in each season for comparison. It was found that the average irradiance energy in the winter was up to 61 less than in the summer. In addition, the study revealed that the day-to-day variation of irradiance in winter (31) was approximately 6.5 times higher than in the summer (4.8). Clearly, the operation of solar power generation systems in the area during winter would face significant day-to-day fluctuations. As a result, this would necessitate frequent operation of backup power systems in order to meet the electrical power load demand. Â© Universiti Malaysia Pahang.